Phytochemical and Antibacterial Profile of Some Liquid Herbal Preparations Sold in Abia State, South-Eastern Nigeria - Pipi, O.G; Nwankwo, E.O; Omodamiro.O.; Nwankwo, C.I. (UMYU Journal of Microbiology Research, 2020)
The use of liquid herbal preparations (LHPs) in the treatment and management of human diseases has long been practiced before the advent of chemotherapy. The beneficial medicinal effects of liquid herbal preparations materials typically result from the secondary products present in the liquid herbal preparations although, it is usually not attributed to a single compound but a combination of the metabolites. This study was carried out to evaluate the antibacterial and phytochemical profile of some liquid herbal preparations in selected markets of Abia State using biochemical and microbiological assay. Preliminary qualitative phytochemical analysis of the liquid herbal preparations inferred the presence of alkaloids (30%), quinones (6%), saponins (7%), flavonoids (19%), glycosides (17%) and tannins (22%). The antibacterial activities of 20 LHPs with bioactive properties against 3 tested clinical bacterial isolates; Staphylococcus aureus, Escherichia coli and Pseudomonas aeruginosa, from hospital samples was evaluated using agar well diffusion methods. Inhibitory zone diameter (IZD) had range of 6-20mm for all bacterial isolates. The pH values of 20 bioactive LHPs range from 3.75-6.76. In conclusion the study revealed consistent presence and varied occurrences of different phytochemicals and antibiotic properties in various herbal preparations which may be taken to indicate that the products are effective. It is also essential to investigate all LHPs to be used as alternative medication in humans, to ensure that the concentrations used will definitely cause inhibition of the specific bacterial strains and meet its therapeutic claims.